Antimicrobial resistance and biofilm formation in rarely reported Salmonella enterica serovars from patients presenting with gastroenteritis in Nairobi, Kenya - Muturi, Peter; Mbae, Cecilia; Kibet, Evans; Njoroge, Peter; Kavai, Susan M.; Ideke, Darius; Jepchirchir, Jessicah; Gunn, John S.; Kariuki, Samuel (Frontiers in Microbiology, 2025)
Non-typhoidal Salmonella infections are a significant global public health concern, causing approximately 150 million illnesses and 60,000 deaths annually, with majority of the cases occurring in low- and middle-income countries. In this study, we used whole genome sequencing to identify and characterize uncommon non-typhoidal Salmonella serovars isolated from patients presenting with gastrointestinal symptoms in the Mukuru area of Nairobi, Kenya. Sixteen less common NTS serovars (excluding Salmonella Typhimurium and S. Enteritidis) were identified from 25 patients, with 1 isolate from blood and 24 from stool samples. The most common serovar was S. Newport, isolated from 6 of the 25 patients, followed by S. Breda (2 patients), S. Eastbourne (2 patients), S. Orion (2 patients) and 12 other serovars, each isolated from a single individual. These serovars displayed diverse antigenic profiles, grouped into 9 distinct serogroups. Antimicrobial resistance profiles and in vitro biofilm formation of the isolates were also assessed. Antimicrobial resistance was detected in three S. Newport strains: two sequence type 31 (ST31) isolates carried the blaTEM−1 and tet(A) resistance genes, while one ST166 isolate carried blaTEM−1, tet(A), aph(6)-Id, and sul2. Biofilm formation varied among the serovars and was enhanced by cholesterol while inhibited by bile. Strong biofilm formation was observed in S. Breda, S. Hann, and S. Eastbourne, whereas S. Chicago and S. Kentucky formed weak biofilms. This study highlights the diversity of NTS serovars circulating in Nairobi and emphasizes on the importance of localized studies in addressing regional variations in NTS epidemiology. To effectively mitigate the burden of NTS infections and curb the spread of AMR, sustained genomic surveillance, the development of advanced diagnostic tools for emerging S. enterica infections, and the implementation of integrated public health interventions are essential.